Membangun Budaya Patuh Hukum Dari Perspektif Law Enforcement - R.A. Kadarmanta; Evita Vebrianti Wulandari; Muslim, Muslim (Jurnal Ekonomi dan Bisnis Digital, 2025)
Building a law-abiding culture in society through a profesional approach to law enforcement is an important element in realizing order and social justice. Profesional law enforcement plays a role in forming and maintaining a law-abiding culture. Law enforcers, including the police, prosecutor's office and judiciary, have a significant influence in ensuring firm, humane and fair law enforcement. The competence, integrity and profesional attitude of law enforcers have been able to become a model for society in complying with the law. The profesionalism of law enforcement requires supervision and accountability to increase public trust. The consistent attitudes and behavior of law enforcers in enforcing the law without discrimination or abuse of power, has a positive impact on society. This research aims to describe the role of law enforcement profesionalism in creating a law-abiding culture, in order to provide recommendations to the government and law enforcement agencies. The method used in the research is a qualitative method by examining primary and secondary data. The research results show that building a law-abiding culture is greatly influenced by the profesionalism of law enforcement. However, it is also recognized that the challenge in building a law-abiding culture is that there are still practices by law enforcement officers who abuse their authority and commit crimes of corruption. There is a need for synergy between law enforcement, government and society in order to create a legal system that is fair, transparent and accountable.